2017
DOI: 10.5815/ijisa.2017.04.05
|View full text |Cite
|
Sign up to set email alerts
|

Combining Different Approaches to Improve Arabic Text Documents Classification

Abstract: Abstract-The objective of this research is to improve Arabic text documents classification by combining different classification algorithms. To achieve this objective we build four models using different combination methods.The first combined model is built using fixed combination rules, where five rules are used; and for each rule we used different number of classifiers. The best classification accuracy, 95.3%, is achieved using majority voting rule with seven classifiers, and the time required to build the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
0
17
0
2
Order By: Relevance
“…In many cases, ensemble algorithms have shown the results which were higher than SVM, multilayer neural network, and k-NN algorithm. Nevertheless, recent studies have shown that this does not always lead to an improvement in quality when applied to natural language texts (Abuhaiba and Dawoud, 2017), apart from requiring significant computational resources.…”
Section: Boosting Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, ensemble algorithms have shown the results which were higher than SVM, multilayer neural network, and k-NN algorithm. Nevertheless, recent studies have shown that this does not always lead to an improvement in quality when applied to natural language texts (Abuhaiba and Dawoud, 2017), apart from requiring significant computational resources.…”
Section: Boosting Algorithmsmentioning
confidence: 99%
“…Based on works (Abuhaiba and Dawoud, 2017;Bourgonje et al 2018;Liu et al 2017;Semberecki and Maciejewski, 2017), it is possible to identify the models of machine learning that are most suitable for classification of textual data. Such models are: logistic regression, random forest, SVM, and artificial neural network (both feedforward and LSTM).…”
Section: Influence Of Number Of Classes On the Quality Of Classificationmentioning
confidence: 99%
“…In [15] built four models by combining different approaches to improve Arabic text documents classification. The first combined model is built using fixed combination rules.…”
Section: Related Workmentioning
confidence: 99%
“…They have used components in accordance with generic QAS architecture, namely: questions analyzer, document retrieval, and answers finder. They also used TfxIDF [52] and cosine similarity techniques to find answers. Next, in [25] they did hybrid system between QAS and Casebased Reasoning (CBR).…”
Section: State Of the Art In Indonesian Questionmentioning
confidence: 99%